A Recombinant Avian Infectious Bronchitis Virus Expressing a Heterologous Spike Gene Belonging to the 4/91 Serotype - Armesto, Maria (Public Library of Science, 2011)
We have shown previously that replacement of the spike (S) gene of the apathogenic IBV strain Beau-R with that from the pathogenic strain of the same serotype, M41, resulted in an apathogenic virus, BeauR-M41(S), that conferred protection against challenge with M41 [1]. We have constructed a recombinant IBV, BeauR-4/91(S), with the genetic backbone of Beau-R but expressing the spike protein of the pathogenic IBV strain 4/91(UK), which belongs to a different serogroup as Beaudette or M41. Similar to our previous findings with BeauR-M41(S), clinical signs observations showed that the S gene of the pathogenic 4/91 virus did not confer pathogenicity to the rIBV BeauR-4/91(S). Furthermore, protection studies showed there was homologous protection; BeauR-4/91(S) conferred protection against challenge with wild type 4/91 virus as shown by the absence of clinical signs, IBV RNA assessed by qRT-PCR and the fact that no virus was isolated from tracheas removed from birds primarily infected with BeauR-4/91(S) and challenged with IBV 4/91(UK). A degree of heterologous protection against M41 challenge was observed, albeit at a lower level. Our results confirm and extend our previous findings and conclusions that swapping of the ectodomain of the S protein is a precise and effective way of generating genetically defined candidate IBV vaccines.